UJI AKTIVITAS ANTIBAKTERI FORMULASI SEDIAAN GEL HAND SANITIZER EKSTRAK ETANOL DAUN PALA (Myristica fragrans Houtt) TERHADAP BAKTERI Staphylococcus epidermidis DAN Streptococcus sp - Sanjaya, Angga Nugraha; Sari, Tio Ranti (Jurnal Penelitian Farmasi Dan Herbal, 2025)
The pala leaves contain alkaloids, flavonoids, saponins, tannins, and steroids which high antiseptic and antibacterial effects. The goal of the research make a formulation of hand sanitizer gel with etanol extreact by pala leaves (Myristica fragrans Houtt) as the antibacterial againt the Staphylococcus epidermidis and Streptococcus sp bacteria with CMC-Na base. Pala leaves hand sanitizer gel with etanol extract was formulation I 5%, formulation II 10%, and formulation III 15%. The method used in this study was antibacterial testing method used is the disc diffusion technique. Hand sanitizer gel is tested for the physical properties including organoleptic test, pH test, homogeneity test, and spreadability test. Hand sanitizer gel which has antibacterial activity against the Staphylococcus epidermidis and Streptococcus sp, bacteria is second (III) formulation in with concentration 15% that has an inhibition zone of 17 mm on bacteria Staphylococcus epidermidis and 16,86 mm on bacteria Streptococcus sp, mean while in formulation II with concentration 10% that has an inhibition zone of 13,16 mm on bacteria Staphylococcus epidermidis ang 13,16 on bacteria Streptococcus sp, mean while in formulation I with concentration 5% that has an inhibition zone of 12,02 mm on bacteria Staphylococcus epidermidis and 12,16 mm on bacteria Streptococcus sp, and the last positive control (nuvo gel hand sanitizer) that has an inhibition 17,73 mm on bacteria Stahylococcus epidermidis and 17,69 mm on bacteria Streptococcus sp. The final results of the research indicate, there is an ability of hand sanitizer gel pala leaves (Myristica fragrans Houtt) extract to prevent the growth of Staphylococcus epidermidis and Streptococcus sp bacteria with concentration of 15% hand sanitizer gel preparation.